Pengadaan Tanah dalam Hutan Konservasi: Pengalaman Pembebasan Lahan Jalan Tol Balikpapan-Samarinda di Kawasan Taman Hutan Raya - Ilmadianti, Ilmadianti; Salim, M Nazir (Tunas Agraria, 2024)
The existence of the land acquisition object for the construction of the Balikpapan-Samarinda toll road, which has the status of the Bukit Soeharto Grand Forest Park (Tahura) area, raises problems, namely being forced to change the spatial layout and provide compensation to the community because at the Tahura location there is land control by the community. This research aims to explain the mechanism for changing the designation of some conservation forest areas to Allocation for Other Uses (APL), look at the consequences of changing the designation of forest areas, and explain the process of compensation to communities that control APL in the "former" Tahura area. The research method used is a socio-legal method with a document study and field study approach. The results of the research show that the change in the designation of some forest areas to APL is carried out through a mechanism for changing the designation of forest areas for provincial areas, the status of APL land in former forest areas is state land, and the provision of compensation for communities that control APL in former forest areas only covers objects that are above the ground. Changing conservation forests to APL is a compromise effort, even though the solution seems forced. The compensation is considered unfair because the government relies more on normative arguments that do not benefit the community.   Keberadaan obyek pengadaan tanah untuk pembangunan jalan tol Balikpapan-Samarinda yang berstatus Kawasan Taman Hutan Raya (Tahura) Bukit Soeharto menimbulkan persoalan, yakni terpaksa merubah tata ruang dan ganti rugi kepada masyarakat, karena di lokasi Tahura terdapat penguasaan tanah oleh masyarakat. Penelitian ini ingin menjelaskan mekanisme perubahan peruntukan sebagian kawasan hutan konservasi menjadi Alokasi Penggunaan Lain (APL), melihat konsekuensi perubahan peruntukan kawasan hutan, dan menjelaskan proses ganti rugi kepada masyarakat yang menguasai APL pada “bekas” kawasan Tahura. Metode penelitian yang digunakan adalah metode sosio-legal dengan pendekatan studi dokumen dan studi lapangan. Hasil penelitian menunjukkan bahwa, perubahan peruntukan sebagian kawasan hutan menjadi APL dilakukan melalui mekanisme perubahan peruntukan kawasan hutan untuk wilayah provinsi, status tanah APL bekas kawasan hutan adalah Tanah Negara, dan pemberian ganti kerugian bagi masyarakat yang menguasai APL bekas kawasan hutan hanya meliputi benda-benda yang berada di atas tanah. Perubahan hutan konservasi menjadi APL adalah upaya kompromi yang dilakukan sekalipun jalan keluarnya terkesan dipaksakan, ganti rugi yang dianggap tidak adil, karena pemerintah lebih bersandar pada argumen normatif yang tidak menguntungkan masyarakat.